(untitled) (Academia Journal of Medicine, 2026)
Capillary hemangiomas are benign vascular proliferations that commonly present in childhood but can persist or appear in adulthood. This case report discusses a rare presentation of an extensive capillary hemangioma involving the maxillofacial region. The patient presented with progressive swelling over three months, with significant facial asymmetry. Diagnosis was confirmed through clinical, radiological, and histopathological examination. The lesion was surgically excised, with post-operative recovery documented. This case highlights the clinical presentation, diagnostic approach, and surgical management of capillary hemangiomas in the maxillofacial region. A comprehensive discussion is included to explore the histopathological features, pathogenesis, differential diagnoses, psychosocial considerations, and therapeutic approaches including current advancements and consensus guidelines.